Functionalized chitosan nanoparticles for cutaneous delivery of a skin whitening agent: an approach to clinically augment the therapeutic efficacy for melasma treatment. (31st December 2022) - Hatem, Shymaa; Elkheshen, Seham A.; Kamel, Amany O.; Nasr, Maha; Moftah, Noha H.; Ragai, Maha H; Elezaby, Reham S.; El Hoffy, Nada M.
Abstract: The increase in the production of melanin level inside the skin prompts a patient-inconvenient skin color disorder namely; melasma. This arouses the need to develop efficacious treatment modalities, among which are topical nano-delivery systems. This study aimed to formulate functionalized chitosan nanoparticles (CSNPs) in gel form for enhanced topical delivery of alpha-arbutin as a skin whitening agent to treat melasma. Ionic gelation method was employed to prepare α-arbutin-CSNPs utilizing a 2 4 full factorial design followed by In vitro, Ex vivo and clinical evaluation of the nano-dispersions and their gel forms. Results revealed that the obtained CSNPs were in the nanometer range with positive zeta potential, high entrapment efficiency, good stability characteristics and exhibited sustained release of α-arbutin over 24 h. Ex vivo deposition of CSNPs proved their superiority in accumulating the drug in deep skin layers with no transdermal delivery. DSC and FTIR studies revealed the successful amorphization of α-arbutin into the nanoparticulate system with no interaction between the drug and the carrier system. The comparative split-face clinical study revealed that α-arbutin loaded CSNPs hydrogels showed better therapeutic efficacy compared to the free drug hydrogel in melasma patients, as displayed by the decrease in: modified melasma area and severity index (mMASI) scores, epidermal melanin particle size surface area (MPSA) and the number of epidermal monoclonal mouse anti–melanoma antigen recognized by T cells-1 (MART-1) positive cells which proved that the aforementioned system is a promising modality for melasma treatment.